Facile Synthesis of 2- and 3-Substituted Indoles Using a Catalytic Amount of Pd/C and 1-Octene System - Dong, Xu; Matsubara, Ryosuke; Hayashi, Masahiko (Synthesis, 2024)
A novel and efficient synthesis of 3- and 2-substituted indoles starting from 2-(2-nitro-1-phenylethyl or 2-nitro-1-alkyl)cyclohexanones and 1,4-diketones, respectively, using a catalytic amount of Pd/C and 1-octene system is reported.
Keywords: 2- and 3- substituted indoles; Pd/C; 1-octene; one-pot synthesis; nitrone; 5-keto nitroalkanes; 1,4-diketone; ammonium acetate